EVALUATION OF LOCATION SELECTION PROCESS OF LOGISTICS VILLAGES USING ANALYTIC HIERARCHY PROCESS AND ELECTRE METHODS: A CASE STUDY FOR TURKEY - Aksoy, Berna; Gursoy, Mustafa (YILDIZ TECHNICAL UNIV, 2020)
The need for logistics has been one of the biggest issues to be resolved for all settlements in all eras of humanity. Infrastructure problems are likely to occur over lime in cities that have grown more than expected. It is accepted all over the world today that the solution of the logistics problem in such settlements is to improve the infrastructure and balance the transportation demand between different modes of transportation and to establish special centers where integrated activities will be carried out. Choosing the location of these logistics centers by decision makers raises a prioritized cost problem. A subject became widespread in the last decade in Turkey has been selected. The current situation of the logistic villages has been evaluated and a construction ranking has been obtained.This study constituted a verification for the state-ordered construction sequence. It is believed that simple and understandable construction needs can guide decision makers in the logistics village study area.
Keywords: Urban planning; logistics; urban freight transport; logistics village; Multi-Criteria Decision-Making (MCDM); sustainability; TRANSPORT; DECISION; TOPSIS; Engineering